The Public Records Of The State Of Connecticut: From May 1778 to April 1780, at 271-272 (Charles J. Hoadley ed., 1895) - (:unkn) unknown (My University, 1779)
Prohibiting challenging another to fight with a sword, pistol, rapier, or other dangerous weapon. The person challenging shall forfeit one thousand pounds and give sureties for good behavior during life. Violators also prohibited from holding any office of "profit or honor under this State." Failure to pay the fine shall lead to imprisonment for one full year.
Keywords: DUELING